Gaya Hidup Sehat Lansia - Nizar Argyatiyasa; Suprajitno Suprajitno; Wiwin Martiningsih (Journal of Ners and Midwifery, 2015)
Elderly experience physical changes, mental changes, psychosocial changes that would affect the elderly healthy lifestyle. The Method used descriptive design. The population in this research were the elderly who were registered in the territory UPTD Posyandu Health Sukorejo Blitar City in 1493 as the elderly, and the samples taken were 94 elderly Using quota sampling technique. The data was collected by interview based on a questionnaire. The data collection was conducted on 18 May until 18 June 2014. The results showed that the Healthy Lifestyle in the posyandu of elderly in region UPTD Healt Sukorejo Blitar City was good 72.3% (68 elderly). According to the Indonesia Republic healthy Deepartement (1997) in Udayana Psychology of journal (2013), defines a healthy lifestyle attempt to implement good practice in creating a healthy lifestyle and avoid bad habits that can affect health. Researchers found elderly efforts in maintaining the health status most of the elderly was optimal, it indicates that the elderly realize the importance of creating a healthy lifestyle.